Analysis of Nonlinear Responses in Asphalt Pavements Under Nonuniform Loading Using Finite Element Methods : - Kumar, Abhinav (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Civil Engineering